Investigation of the relationship between mineral element levels and serum biochemical parameters in children in Pingyin, China - Li, Xia; Jiao, Yan-ni; Liu, Yu-mei; Liang, Jia-bing; Chen, Jin-dong; Zhou, Jing-yang; Li, Wei; Jia, Xing-bing; Miao, Wan-ping; Zhao, Shu-yong; Zhai, Shi-yong; Hu, Mao-you; et al. (Trace elements and electrolytes, 2016)
Objective: The present study was designed to evaluate the relationship between mineral element levels and the health status of children. Material and methods: A total of 610 healthy children aged from 6 to 12 years (327 boys and 283 girls) from five selected villages in the Pingyin County participated in this study. Information including age, gender, height, weight, and blood pressure (BP) were recorded by health professionals. Blood samples of participants were collected and analyzed. Fourteen serum mineral elements were determined by atomic absorption spectrometer (AAS) and inductively coupled plasma mass spectrometry (ICP-MS). The correlations between serum element concentrations and serum biochemical parameters were investigated. Results: No significant gender difference was found for the tested elements. Significant correlations between age and the levels of copper (Cu) (r = -0.132), magnesium (Mg) (r = 0.114), and cadmium (Cd) (r = 0.152) were obtained. A correlation between body mass index (BMI) and serum Cu (r = -0.165) and zinc (Zn) (r = -0.106) was found. Noticeable inverse correlations of systolic blood pressure (SBP) and diastolic blood pressure (DBP) with serum Cu, chromium (Cr), and nickel (Ni) were observed. There was a positive correlation of SBP and DBP with Cd. In addition, DBP was negatively correlated with selenium (Se) and positively correlated with lead (Pb). The fasting blood-glucose (FBG) was significantly correlated with serum Cr (r = -0.326). The concentration of low-density lipoprotein (LDL) was significantly correlated with Cu (r = -0.234), Cr (r = -0.316), and Se (r = 0.301). The level of total cholesterol (TC) was significantly correlated with iron (Fe) (r = -0.186) and Se (r = 0.117). The triglyceride (TG) level was significantly correlated with Se (r = 0.177). Interrelations of elements were as follows: serum Pb was significantly correlated with levels of Zn (r = -0.107), Se (r = -0.486), and Cd (r = 0.465); Se level was significantly correlated with Cd (r = -0.868) and arsenic (As) (r = -0.10); the level of Zn was significantly correlated with Cu (r = -0.105) and Fe (r = 0.137). Conclusions: Serum element concentrations may influence many biochemical parameters. It is important to measure the trace element status in children because changes and interactions may play an important role in the human metabolism.